Journalism and the Muslim Narrative: Power, Resistance and Change - Haq, Nadia (Routledge Research in Journalism, 2025)
Journalism and the Muslim Narrative presents an empirical analysis of how modern-day journalism practices contribute to the negative bias against Muslims in Britain, to provide an in-depth investigation of how we can better re-conceptualise journalism for our increasingly multicultural societies. For more than 20 years, media activists and academic scholars have highlighted a bias in British newspapers where Muslims are portrayed as the problematic ‘Other’ of British society. This book draws on the representation of Muslims to contribute a critical, empirical analysis of contemporary journalistic practices in multicultural societies. This includes a deeper insight into media audiences and the public, journalism norms and values such as objectivity, balance and freedom of speech, the wider implications of the increasing digitalisation of the media and the tensions between media structures and journalistic agency. As competition with social media heightens pressures on journalists to produce even more sensationalist and polarising coverage about Muslims, this book further offers a critical evaluation of how journalism needs to be re-imagined to realise its civic role in our progressively digitalised and diverse societies. Drawing on the first-hand accounts of newspaper journalists and editors, the author challenges our understanding of journalism and the role that journalists play in uniting, rather than dividing, our diverse societies. This book builds a critical appraisal of academic perspectives from journalism, media and cultural studies, sociology, postcolonial theory and the study of race and religion, and how journalism practices can either perpetuate or challenge discriminatory and divisive narratives about Britain’s Muslim communities. It will be of value to journalism practitioners as well as academics studying journalism, media and communications, cultural studies and race and ethnicity studies